2022
DOI: 10.17221/471/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-based fertiliser improved the yield, quality and fertiliser utilisation of open field tomato in karst mountainous area

Abstract: Biochar-based fertiliser (BF) is beneficial to improve yield and quality, but the effect of BF on open field tomato remains unclear, especially in karst mountainous areas. The objective of this study was to identify the application effect and optimum application rate of BF. A field experiment was carried out in Southwestern China from 2019 to 2020 to study the effects of different application amounts of BF on the yield, quality, nutrients accumulation and fertiliser utilisation of open field tomatoes. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The average dry mass of root, stem, leaf, and fruit; Y; and WUE increased with increasing biochar application. Biochar can promote plant height and leaf growth and significantly increase aboveground dry matter [49,50] . Zhang et al [51] also showed that biochar application can promote the absorption capacity of tomato plants to nutrients and improve tomato yield.…”
Section: Biochar Application Increased Dry Matter Y and Wue Of Tomatomentioning
confidence: 99%
“…The average dry mass of root, stem, leaf, and fruit; Y; and WUE increased with increasing biochar application. Biochar can promote plant height and leaf growth and significantly increase aboveground dry matter [49,50] . Zhang et al [51] also showed that biochar application can promote the absorption capacity of tomato plants to nutrients and improve tomato yield.…”
Section: Biochar Application Increased Dry Matter Y and Wue Of Tomatomentioning
confidence: 99%
“…Pod pepper holds a vital place among economic crops, as it is not only the largest vegetable crop in terms of planting area and production value in southwest China, but also boasts a high nutritional value [31,32]. Numerous field experiments have demonstrated that supplementing chemical fertilizers with biochar can enhance crop yield and soil nutrient levels.…”
Section: Introductionmentioning
confidence: 99%
“…At present, organic remediation materials have received much attention as widely used soil amendments because of their beneficial effects in enhancing crop yield and quality and improving soil quality. Many studies have confirmed that organic remediation materials can overcome or mitigate the barriers to continuous cropping by increasing organic carbon sources and soil microbial diversity ( Su et al., 2022 ; Zhang et al., 2022a ; Zhang et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%